2021
DOI: 10.1186/s12957-021-02132-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Controlling Nutritional Status (CONUT) score predicts short-term outcomes of patients with gastric cancer after laparoscopy-assisted radical gastrectomy

Abstract: Background An emerging prediction tool, the Controlling Nutritional Status (CONUT) score, has shown good assessment ability of postoperative outcomes in cancer patients. This study evaluated the role of the preoperative CONUT score regarding the short-term outcomes of gastric cancer (GC) after laparoscopic gastrectomy. Methods Three hundred and nine GC patients undergoing laparoscopic gastrectomy from January 2016 to June 2019 were analysed, retros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…As a member of the inflammatory cell family, LYM is involved in altering the tumor microenvironment. Patients with low LYM levels were reported to have a worse prognosis than those with high LYM levels (22)(23)(24). In this study, we further explored the factors that affect the development of HIV infectionassociated lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the inflammatory cell family, LYM is involved in altering the tumor microenvironment. Patients with low LYM levels were reported to have a worse prognosis than those with high LYM levels (22)(23)(24). In this study, we further explored the factors that affect the development of HIV infectionassociated lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The CONUT score can also be used as a prognostic predictor for many other solid tumors. Studies have found that the CONUT score is a strong independent predictor of postoperative complications and longterm prognosis in colorectal cancer, 13,[22][23][24] cholangiocarcinoma, 25,26 kidney cancer, 27 esophageal cancer, 28 gastric cancer, 12,29 pancreatic cancer, 30 and liver cancer. 31,32 We established a nomogram based on the CONUT score for accurate prediction of the prognosis of patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…BC cancer prognosis appears to be closely related to the degree of systemic inflammation and nutritional status [29,30]. Although the use of CONUT was previously confined to assessing nutritional status only, more and more evidence has highlighted its ability to predict cancer patient survival [31][32][33]. The various components of the CONUT score-TLC, ALB, and TC, reflect impaired immune defenses, protein reserves, and caloric depletion, respectively.…”
Section: Discussionmentioning
confidence: 99%